Nanorods - Yal&#231, Orhan (IntechOpen, 2012)
The book "Nanorods" is an overview of the fundamentals and applications of nanosciences and nanotechnologies. The methods described in this book are very powerful and have practical applications in the subjects of nanorods. The potential applications of nanorods are very attractive for bio-sensor, magneto-electronic, plasmonic state, nano-transistor, data storage media, etc. This book is of interest to both fundamental research such as the one conducted in Physics, Chemistry, Biology, Material Science, Medicine etc., and also to practicing scientists, students, researchers in applied material sciences and engineers.